In Vitro and In Vivo Activity Evaluations, LC-MS Profiling, Stability Testing, and Capsule Formulation of a Thai Folk Analgesic Herbal Formula - Aiamsa-ard, Tipsuchon; Monton, Chaowalit; Jongcharoenkamol, Jira; Wunnakup, Thaniya; Navabhatra, Abhiruj; Suksaeree, Jirapornchai; Chankana, Natawat; Sudsai, Teeratad (Trends in Sciences, 2025)
The Thai folk analgesic herbal formula, Ya Ka Sai Sen (YKSS), has been traditionally used among patients in rural Thailand, yet its scientific basis remains unexplored. This study evaluated the in vitro antioxidant, anti-inflammatory and cytotoxic properties, along with in vivo acute toxicity and analgesic activities of YKSS. Stability studies and capsule formulation development were also undertaken. Two batches of herbs, harvested at different times, were decocted to yield eight extracts. Total phenolic and flavonoid contents ranged from 100.50 to 179.89 mg GAE/g and 51.43 to 96.19 mg CE/g, respectively. Antioxidant assays demonstrated DPPH IC50 values of 8.74 - 96.19 µg/mL and FRAP values of 2,148.20 - 3,032.97 µmol Fe(II)/g. However, nitric oxide scavenging was below 50%, while inhibition of nitric oxide production in cell-based assays showed IC50 values of 820.93 - 969.13 µg/mL. Anti-lipoxygenase activity was moderate (IC50: 15.50 - 72.75 µg/mL) and cytotoxicity against HepG2 cells varied between 1 - 10 µg/mL. LC-MS analysis identified N-trans-feruloyltyramine and maltose as major compounds in positive and negative ionization modes, respectively. Stability studies showed some samples degraded after one year under ambient conditions. Acute toxicity testing revealed no adverse effects at 2,000 mg/kg in rats. Analgesic evaluation via acetic acid-induced writhing tests showed significant reductions in writhing episodes, whereas no effects were noted in the hot plate test, indicating peripheral nociception inhibition. YKSS was successfully developed into a capsule formulation, demonstrating antioxidant, anti-inflammatory, and analgesic activities with a favorable safety profile. These findings support further exploration of YKSS as a potential therapeutic agent. HIGHLIGHTS Ya Ka Sai Sen exhibited in vitro antioxidant, anti-inflammatory and safety potential. Writhing test suggested peripheral analgesic activity of Ya Ka Sai Sen in rats. LC-MS profiling detected N-trans-feruloyltyramine and maltose in extracts. Ya Ka Sai Sen was formulated into capsules and evaluated for basic quality parameters. GRAPHICAL ABSTRACT